Influence of the Immunostimulant Zerox for Pure Photosynthesis Efficiency of Bukhara-10 Cotton - Atoeva Rukhsora Odilovna (Genius Journals, 2022)
In this article, information about universal and triple contact actional ZEROX immunostimulant at 3 various (1-2-3 l/t and 1-2-3 l/ha+ Surfactant 0.15 l /ha) norms and different (pre-sowing to cotton seed was treated, 2 - 4 true leaves, shading, flowering) periods when it affected to Bukhara 10 cotton on 3 numbers of seedlings is presented. Research has shown, when in pre-sowing of seed 2 l/t and 2 l/ha in vegetation periods of ZEROX immunostimulant in the number of left seedlings 80 - 90,000 plant/ha of Bukhara 10 cotton it was treated, it was determined that the highest pure photosynthesis efficiency was obtained
Keywords: ZEROX immunostimulant,; Bukhara -10; The number of Seedlings; pre-sowing